2013
DOI: 10.1590/brag.2013.029
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade de sementes de amendoim armazenadas no estado de São Paulo

Abstract: ResumoCom os objetivos de avaliar a qualidade fisiológica e sanitária de sementes de amendoim armazenadas no estado de São Paulo, identificar os principais insetos e fungos que ocorrem nessas condições e as possíveis injúrias causadas que possam prejudicar a qualidade dessas sementes, amostragens de lotes das cultivares IAC 886 e IAC 503, produzidas nas safras 2010/11 e 2011/12, foram realizadas em quatro épocas: antes do armazenamento, antes do beneficiamento, após o beneficiamento e após o tratamento químico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0
13

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 9 publications
2
15
0
13
Order By: Relevance
“…In addition, these conditions may favor fungal and insect activity, thus reducing seed quality (Christensen and Kaufmann 1965). Thus, in São Paulo, the occurrence of peanut seed lots with germination percentage is often lower than the standard established for marketing (60%), due to high rates of infection caused by fungi and insects (Santos et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, these conditions may favor fungal and insect activity, thus reducing seed quality (Christensen and Kaufmann 1965). Thus, in São Paulo, the occurrence of peanut seed lots with germination percentage is often lower than the standard established for marketing (60%), due to high rates of infection caused by fungi and insects (Santos et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…At lower relative humidity, the growth of these fungi is arrested. Among these fungi, those belonging to the genus Fusarium (Thiessen and Woodward 2012;Santos et al 2013) have been reported to cause rot and reduced physiological potential in peanut seeds.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations